Multi-source data security protection of smart grid based on combination key - Jian GAO; Wenbin CHEN; Jianmin PANG; Huadong YU; Guorui SONG (Dianxin kexue)
As an important infrastructure of power system,power communication network has deployed a large number of widely distributed business terminals and communication terminals,whose data security is related to the safe and stable operation of the entire power network.In order to avoid the situation that the information cannot be safely exchanged due to the shortage of keys.The sharding and combination technology based on keys was proposed to realize the expansion of limited keys,so as to solve the problem of a large number of keys needed for multi-node and mul-ti-service.Firstly,a sharding scheme was obtained according to different conditions.A key was divided into several dif-ferent sub-key pieces,and then a new key was generated by combining these key pieces and distributed to different ter-minals in the system.A large number of combined keys generated were conducive to update key ,which could ensure the data service “one at a time” and effectively enhance the communication system's ability to resist damage and invasion.Through analysis and calculation,the effectiveness of this method in realizing real-time update of a large number of ter-minal business keys with limited keys was further verified,and data secure communication was realized.